Analysis of surgery rates among 25 national collegiate athletic association sports. Issue 1 (2nd January 2022) - Taree, Amir; Charen, Daniel; Huang, Hsin-Hui; Poeran, Jashvant; Colvin, Alexis
ABSTRACT: Objectives: While injuries among collegiate athletes are common and well-studied, there have been no studies comparing which sports and injury types have the highest operation rates. This information would be valuable for athlete governing bodies and providers to improve player safety. Our hypothesis was the surgery incidence rates vary substantially between sports and injury types, with football and knee injuries representing the sport and injury type with the highest respective surgery rates. Methods: This was a descriptive epidemiology study of all injuries requiring surgery as recorded in the National Collegiate Athletic Association (NCAA) Injury Surveillance Program (ISP) for academic years 2004–2005 to 2013–2014. Surgery incidence rates (and 95% confidence intervals, CI) were calculated for each sport (per 10, 000 athletic exposures [AE]) and for the most common injury types, by academic year. In addition, absolute numbers of performed surgeries were calculated as well as rates of return to sport. Results: Sports with the highest surgery incidence rate (per 10, 000 AEs) were women's gymnastics (8.9; 95% CI 7.2–10.9), men's football (6.1; 95% CI 5.8–6.4), and men's wrestling (5.3; 95% CI 4.5–6.3). Absolute numbers of injury-related surgeries performed were greatest for men's football (n = 31, 043), women's basketball (6, 625), and men's basketball (5, 717). Anterior cruciate ligament tears had the greatest surgery incidence rate per 100, 000 AEs for all sports combined (7.95; 95% CI = 7.5 to 8.5), and also represented the injuries with the lowest rate of return to sport. Conclusion: Women's gymnastics, men's football, and men's and women's basketball are NCAA sports with an elevated risk of injury requiring of surgery. The results from this study can guide the NCAA and providers regarding which sports should be the focus of future research, new injury prevention strategies, and healthcare personnel allocation during events.